PEMBUATAN DAN MODIFIKASI KARBON AKTIF PELEPAH KELAPA SAWIT (Cocus nucifera L.) SEBAGAI ADSORBEN METILEN BIRU (PREPARATION AND MODIFICATION OF ACTIVATED CARBON FROM PALM OIL (Cocus nucifera L.) AS ADSORBENT OF BLUE METHYLENE) - Risma Achmad; St Fauziah; Muhammad Zakir (Indonesian Journal of Pure and Applied Chemistry, 2020)
The methylene blue dye adsorbed by activated carbon from oil palm fronds modified with H2SO4 has been carried out. This study aims to utilize activated carbon from palm oil frond waste (Cocus nucifera L.) as an adsorbent to adsorb toxic methylene blue dye in textile industrial wastewater. The method consisted of several steps, namely: carbonization, carbon activation using 0.3M HCl activator, surface modification, and identification of functional groups using FTIR, characterization of the adsorbent material using SEM, BET, and surface area analysis with methylene blue. The optimal adsorption time of methylene blue by activated carbon is 20 minutes, longer than modified activated carbon which is 15 minutes. Adsorption of methylene blue by activated carbon and modified activated carbon according to the Langmuir isothermal model. The adsorption capacity of activated carbon was lower, namely 9.7847 mg / g compared to the adsorption capacity of modified activated carbon, which was 10.7642 mg / g. This proves that the active carbon modified by H2SO4 is better used as an adsorbent for adsorbing methylene blue dye